Pengaruh Brand Image, Brand Trust, dan Electronic Word of Mouth Terhadap Keputusan Pembelian Produk di Fore Cofee Gatsu Tengah - Nia Yunita, Ni Kadek; Raka Suardana, Ida Bagus (Economic Reviews Journal, 2025)
The growth of the modern coffee industry in Indonesia has increased significantly in line with lifestyle changes and advancements in digital technology. This development encourages businesses, including Fore Coffee Gatsu Tengah, to understand the determinants that influence consumer purchasing decisions. This study aims to analyze the influence of brand image, brand trust, and electronic word of mouth (e-WOM) on consumer purchasing decisions at Fore Coffee Gatsu Tengah. The research employed a quantitative approach with an associative design. The sample was determined using the Slovin formula and involved more than 100 respondents. Data were collected through questionnaires using a Likert scale, while data analysis was conducted using multiple linear regression complemented by the F-test, t-test, and coefficient of determination (R²) with the assistance of SPSS software. The results indicate that brand image, brand trust, and e-WOM simultaneously have a significant influence on purchasing decisions. Partially, brand trust and e-WOM show significant effects, whereas brand image demonstrates a weaker influence compared to the other variables. The Adjusted R² value of 0.523 indicates that 52.3% of the variation in purchasing decisions can be explained by the three independent variables, while the remaining 47.7% is influenced by other factors outside the research model. The findings contribute theoretically to the field of marketing management, particularly regarding the roles of brand image, brand trust, and e-WOM in shaping consumer behavior. Practically, the results serve as a reference for Fore Coffee in formulating more effective marketing strategies to enhance competitiveness and strengthen consumer purchasing decisions.